Pemanfaatan Cyber Extension melalui Telepon Genggam oleh Petani Anggrek di Taman Anggrek Ragunan, Jakarta Selatan - Aira Putri Eri Dasli; Pudji Muljono; Djoko Susanto (Jurnal Penyuluhan, 2015)
Cyber extension is one of the modern technology which can be utilized by the farmers, extension workers, and Business actors to obtain informations and develop agricultural business. The purpose of this study was to analyze relationship between characteristics of respondents and environmental with the farmers behavior in utilizing cyber extension (Hp and internet) to support farming activities as well as the utilized on farm orchid plants. This study is descriptive correlational type of survey method. Research conducted at the Ragunan Orchid Park, South Jakarta, Jakarta Province. The sample were all growers of orchids as many as 35 people. The behavior of farmers for using cyber media, especially utilized of mobile phones. It also had a positive utilized in the development of farming, especially in marketing orchids in town and out of town. So, the farmers increase consumer and profit.Keywords: cyber extension, extension workers, utilized, handphone